2017
DOI: 10.1007/s10238-017-0453-6
|View full text |Cite
|
Sign up to set email alerts
|

Associations between circulating levels of adipocytokines and abdominal adiposity in patients after acute pancreatitis

Abstract: Adipocytokines are strongly associated with abdominal adiposity during the course of acute pancreatitis (AP). This study investigated associations between a panel of adipocytokines and abdominal adiposity in AP patients after hospital discharge, as well as the effect of several covariates. Fasting venous blood samples were collected to measure adiponectin, interleukin 6, leptin, monocyte chemoattractant protein 1, tumour necrosis factor α (TNFα), resistin, and retinol-binding protein 4. Waist circumference (WC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 45 publications
2
29
0
Order By: Relevance
“…Specifically, IFD exacerbates the inflammatory responses in AP, worsening its clinical course . It is now increasingly recognized that inflammation of the pancreas is not completely reversible and that chronic low‐grade inflammation persists in many individuals after AP . At least two out of five individuals develop new‐onset prediabetes and diabetes after AP (NODAP) .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, IFD exacerbates the inflammatory responses in AP, worsening its clinical course . It is now increasingly recognized that inflammation of the pancreas is not completely reversible and that chronic low‐grade inflammation persists in many individuals after AP . At least two out of five individuals develop new‐onset prediabetes and diabetes after AP (NODAP) .…”
Section: Introductionmentioning
confidence: 99%
“…At least two out of five individuals develop new‐onset prediabetes and diabetes after AP (NODAP) . Moreover, excess abdominal adiposity also contributes to low‐grade inflammation after AP . However, to the best of our knowledge, no study has investigated comprehensively the associations between IFD and body composition as well as indices of insulin secretion, indices of insulin sensitivity, incretins and related peptides in individuals with prediabetes and diabetes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Human adipose tissue depots have been identified as a major site of pro-calcitonin mRNA with recent studies reporting calcitonin secretion from adipocytes in obese individuals with associated insulin resistance (15,16). Increasing body of evidence shows that abdominal adiposity is also involved in metabolic dysregulations following an episode of acute pancreatitis (17)(18)(19). Further, elevated amylin levels have been reported in patients with chronic alcoholic pancreatitis and abnormal glucose metabolism (13), with similar findings reported in a study involving patients with acute pancreatitis that found a significant correlation between amylin and abnormal glucose metabolism (20,21).…”
Section: Introductionmentioning
confidence: 99%